A Personalized Multi-Channel FES Controller Based on Muscle Synergies to Support Gait Rehabilitation after Stroke - Ferrante, Simona; Chia Bejarano, Noelia; Ambrosini, Emilia; Nardone, Antonio; Turcato, Anna M.; Monticone, Marco; Ferrigno, Giancarlo; Pedrocchi, Alessandra (Frontiers in Neuroscience, 2016)
It has been largely suggested in neuroscience literature that to generate a vast variety of movements, the central nervous system (CNS) recruits a reduced set of coordinated patterns of muscle activities, defined as muscle synergies. Recent neurophysiological studies recommended the analysis of muscle synergies to finely assess the patient’s impairment, to design personalized interventions based on the specific nature of the impairment, and to evaluate the treatment outcomes. In this scope, the aim of this study was to design a personalized multi-channel functional electrical stimulation (FES) controller for gait training, integrating three novel aspects: 1) the FES strategy was based on healthy muscle synergies in order to mimic the neural solutions adopted by the CNS to generate locomotion; 2) the FES strategy was personalized according to an initial locomotion assessment of the patient and was designed to specifically activate the impaired biomechanical functions; 3) the FES strategy was mapped accurately on the altered gait kinematics providing a maximal synchronization between patient’s volitional gait and stimulation patterns. The novel intervention was tested on two chronic stroke patients. They underwent a 4-week intervention consisting of 30-minute session of FES-supported treadmill walking three times per week. The two patients were characterized by a mild gait disability (walking speed>0.8m/s) at baseline. Before treatment both patients presented only three independent muscle synergies during locomotion, resembling two different gait abnormalities. After treatment, the number of extracted synergies became four and they increased their resemblance with the physiological muscle synergies, which indicated a general improvement in muscle coordination. The originally merged synergies seemed to regain their distinct role in locomotion control. The treatment benefits were more evident for one patient, who achieved a clinically important change in dynamic balance (Mini-Best Test increased from 17 to 22) coupled with a very positive perceived treatment effect (GRC=4). The treatment had started the neuro-motor relearning process also on the second subject, but 12 sessions were not enough to achieve clinically relevant improvements. This attempt to apply the novel theories of neuroscience research in stroke rehabilitation has provided promising results, and deserves to be further investigated in a larger clinical study.